Synthesis and surface functionalization of Fe3O4-SiO2 core-shell nanoparticles with 3-glycidoxypropyltrimethoxysilane and 1,1′-carbonyldiimidazole for bio-applications - Thi Kieu Hanh, Ta
Tài liệu do giáo viên cung cấp